African Pastors’ Virtual Ministry from South Korea - Hirome, David (International bulletin of mission research, 2024)
The massive shift of ministry from physical to virtual spaces as occasioned by the Covid-19 pandemic led to an explosion in virtual ministry. The proliferation of social media within diverse areas of human life continues to present important ramifications for present and future church ministry. This article presents the findings of a qualitative research study into the virtual ministry of thirteen African pastors in Korea to their people back home and in so doing highlights the importance of Christian mission from an African diasporic view. The purpose of this study was to understand the experiences of African pastors in Korea who conducted virtual ministry to their congregation back home in the time of Covid-19. The grounded theory of this study was that African virtual pastoring from Korea during Covid-19 was driven by a search for community, used the prevalent and yet unreliable or problematic social media platforms, as a means to carry out interactive ministries and often extended beyond their home audiences. It is also revealed that the African pastors forged a mediated space through their virtual ministry even as they negotiated their distance and belonging in South Korean society.